The Spectrum of Weed Species and Fungal Pathogens in Stands of Alternative Fodder Crop Lolium Multiflorum Var. Westerwoldicum Growing up in a Drought-Prone Area in the Czech Republic - Leoš Kadlček (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2021)
Annual ryegrass (Lolium multiflorum var. westerwoldicum) is cultivated in various areas of the world as a feed for live stock. Efforts to improve the production of high-quality feed in the face of deepening climate change have increased the demand for growing non-traditional types of crops, including ryegrass. The aims of the research were to determine the spectrum of weed and fungal pathogen species and to assess dangerous species of weeds and pathogens which negatively affect forage crops of annual ryegrass grown in dry conditions. In 2018-2019 the occurrence of weeds and fungal pathogens of ryegrass was evaluated in field conditions. The assessed lands were located in dry climatic conditions of South Moravia (Czech Republic). The vegetation recording was done on phytosociological plots of 12 m2. A total of 57 weed species were identified in the plots, where 12 species were toxic and 16 species were undesirable. The most problematic weeds and poisonous species were: Aethusa cynapium, Datura stramonium, Equisetum palustre, Euphorbia helioscopia, Fumaria officinalis and Solanum nigrum, which can cause health problems if present in cattle feed. A pathogenic infection caused by Blumeria graminis, Puccinia graminis var. graminicola and P. coronata var. coronata, Gaeumannomyces graminis and Drechslera sp. was identified on the ryegrass plants in the experimental plots during the vegetation. Blumeria graminis was the most abundant, but it did not endanger the final feed. The data was processed by CCA analysis.